Frequency-resolved cross-correlation between XUV high harmonics and IR fundamental laser pulses by transient multiphoton absorption spectroscopy in gases - Juliette Dubois; Adrien Leblanc; Julien Gautier; Fabien Tissandier; Léonardo Rico; Boris Vodungbo; Jérémie Caillat; Camille Lévêque; Richard Taïeb; Guillaume Lambert (Physical Review Research)
Numerous methods have been developed to retrieve the full temporal properties of ultrafast infrared laser pulses, and are presently implemented on laser facilities all around the world. We present here a technique, developed for the XUV domain, suitable to characterize any femtosecond to picosecond pulse, that can be routinely produced on the high variety of existing sources of high harmonics, free electron lasers, and plasma-based XUV lasers. Especially, the versatility is such that no limitation on any property of any potential source exists. Our technique relies on a frequency-resolved cross-correlation measurement between an infrared pulse and an XUV pulse, combined with a transient multiphoton absorption in gases. It provides temporal information on the longest of the two pulses: intensity profile, pulse duration, and possible presence of pre- or postpulses. More importantly, the measurement of resolved XUV spectra and the use of iterative phase-retrieval algorithms give access to phase information. The simplicity of the technique makes its implementation on various XUV beamlines straightforward.